Nutritional Status of Cocoa in Papua New Guinea - Nelson, P.; Webb, M.; Berthelsen, S.; Curry, George; Yinil, D.; Fidelis, C.; Fisher, M.; Oberthur, T. (International Plant Nutrition Institute, 2011)
Leaf and soil nutrient status was surveyed at 63 cocoa sites in Papua New Guinea (PNG) to determine if productivity is nutrient limited and how these limitations might be overcome. Nitrogen and Fe were deficient in >89% of the sites and P was deficient in about 25%. Management of cocoa in PNG must improve dramatically for the industry to prosper. Successful management schemes should consider a full systems context due to the complexity of socio-economic-agronomic factors. Improved nutrient management will require development of tools directed towards better foliar analysis.